724 Do Renal Mass Biopsies Influence Patient Management? a Case Series Study in a Tertiary Hospital. (19th August 2022) - Kretzmer, L; Nour, E; Akinjise-Ferdinand, O; Mohammed, M; Bhatt, R
Abstract: In recent years renal mass biopsy (RMB) has been increasingly adopted to guide management in patients with renal lesions. Indications include the evaluation of renal masses or cysts, and diagnosis prior to initiating targeted chemotherapy or ablation. A case series of 232 RMBs was collected from 2009–2020. Inclusion criteria were RMBs taken from native kidneys. Participants' mean age was 64.7 years (SD = 13.57 years), with 67% being male. The diagnostic rate of RMB was 78.45% ( n = 182/232). Whether masses were solid or cystic did not influence diagnostic rate ( p = .94143). Positive predictive value (PPV) of RMB compared with surgical histology was .8775. Only 1.3% ( n = 3/232) of cases had significant complications. Patients with non-diagnostic biopsies were more likely to be managed with surveillance alone (56.0% vs 32.4%; p < .05). Diagnostic RMBs did not statistically influence whether patients had surgical management ( p = .188914). Of non-diagnostic RMBs, 100% ( n = 7/7) of patients with surgical histology had renal cell carcinoma (RCC). RMB has specific implications in two special populations: In small renal masses, PPV of RMB increased to 1.0. 16.7% ( n = 3/18) of patients diagnosed with oncocytoma at RMB had a diagnosis of RCC. RMBs are safe with a high diagnostic rate. However, it seems to not influence definitive patient management. Clinicians should be wary when dealing with special populations. Results must be viewed in the context of the patient's history and imaging, and management should be determined using a multi-disciplinary approach.